Optimalisasi Layanan Publik Badan Intelijen Negara Dalam Perspektif Global Cybersecurity Index - M. Yusuf Samad (AL-ULUM: JURNAL SAINS DAN TEKNOLOGI, 2021)
Indonesia is currently ranked 24th in the Global Cybersecurity Index (GCI) 2020. Indonesia's ranking can be improved by improving the assessment pillars of the GCI survey, one of the efforts is to improve the cyber security system of government agencies through Security Assessment. For this reason, the purpose of this study is to provide alternative solutions in order to optimize the public services of the State Intelligence Agency (BIN) in the form of Security Assessment in the perspective of the GCI 2020 survey. This research is a qualitative research using data related to BIN public services and then juxtaposed with data from the Global Cybersecurity survey. Index 2020 as a reference. The results of the study indicate that the optimization of the Security Assessment can be done by implementing cyber counterintelligence and optimizing the publication of services by paying attention to the rules of intelligence secrecy. With the optimization of the Security Assessment, it will affect the assessment of the Technical and Organizational pillars in the GCI survey so that it is expected that Indonesia's ranking will increase in the next survey.